IDIOMS IN THE JUMANJI : WELCOME TO THE JUNGLE MOVIE - Happy Fransiska Tafonao (Universitas Nias Raya, 2026)
This study was conducted to investigate idioms in the movie Jumanji: Welcome to the Jungle. The purpose of this study is to determine the types of idioms and describe the meaning of idioms contained in the movie Jumanji: Welcome to the Jungle. This research is a qualitative research. The researcher collected and classified the data into seven types of idioms suggested by O'Dell & McCarthy and after obtaining the data, the researcher analyzed the data by applying data reduction, data display, conclusion drawing and verification. The results of this study show that there are various kinds of idioms found in the movie Jumanji: Welcome to the Jungle based on the type of idiom, namely 5 similes, 3 binomials, 5 proverbs, 3 euphemisms, 3 clichés, 8 fixed statements, and 4 other languages. Each idiom has its own meaning and is interpreted based on the context in which it is used. Idioms are obviously most prevalent in movies and really help people to enrich their vocabulary and broaden their understanding of all expressions in English. The researcher suggests students to read this thesis in order to know the context of idioms and also interpret the meaning of idioms. In addition, the researcher also suggests to other researchers to complete further research better and provide more explanations and can also use this research as their reference.